Cardiovascular Autonomic Function Changes and Predictors During a 2-Year Physical Activity Program in Rheumatoid Arthritis: A PARA 2010 Substudy - Hupin, David; Sarajlic, Philip; Venkateshvaran, Ashwin; Fridén, Cecilia; Nordgren, Birgitta; Opava, Christina H.; Lundberg, Ingrid E.; Bäck, Magnus (Frontiers in Medicine, 2021)
Background: Chronic inflammation leads to autonomic dysfunction, which may contribute to the increased risk of cardiovascular diseases (CVD) in patients with rheumatoid arthritis (RA). Exercise is known to restore autonomic nervous system (ANS) activity and more particularly its parasympathetic component. A practical clinical tool to assess autonomic function, and in particular parasympathetic tone, is heart rate recovery (HRR). The aim of this substudy from the prospective PARA 2010 study was to determine changes in HRR post maximal exercise electrocardiogram (ECG) after a 2-year physical activity program and to determine the main predictive factors associated with effects on HRR in RA. Methods: Twenty-five participants performed physiotherapist guided aerobic and muscle strength exercises for one year and were instructed to continue the unsupervised physical activity program autonomously in the next year. All participants were examined at baseline and at years one and two with a maximal exercise ECG on cycle ergometer. HRR was measured at 1, 2, 3, 4, and 5 min following peak heart rate during exercise. Machine learning algorithms with the elastic net linear regression models were performed to predict changes in HRR1 and HRR2 at one year and two years of the PARA program. Results: Mean age was 60±9.8 y, range of 41-73 y (88% women). Both HRR1 and HRR2 increased significantly from baseline to year 1 with guided physical activity and decreased significantly from year 1 to year 2 with unsupervised physical activity. Blood pressure response to exercise, low BMI and muscular strength were the best predictors of HRR1/HRR2 increase during the first year and HRR1/HRR2 decrease during the second year of the PARA program. Conclusion: ANS activity in RA assessed by HRR was improved by guided physical activity, and machine learning allowed to identify predictors of the HRR response at the different time points. HRR could be a relevant marker of the effectiveness of physical activity recommended in patients with RA at high risk of CVD. Very inactive and/or high CVD risk RA patients may get substantial benefits from a physical activity program.